Targeted Therapy for Cancer in the Genomic Era. Issue 4 (July 2015) - Afghahi, Anosheh; Sledge, George W.
<x xml:space="preserve">Abstract</x> Abstract The advent of cancer genomics has led to the development of many highly successful targeted therapies, primarily inhibitors of growth factor receptors and related kinases, including imatinib for chronic myeloid leukemia and trastuzumab for HER2-positive breast cancer. This approach has become highly successful for certain cancers. However, as the list of targeted therapies expands, their efficacy becomes more limited, and toxicity accumulates. What we have learned in the past decades is that while the targeted therapeutics approach may be highly successful in less complex tumors, cancers defined by carcinogen-induced genomic chaos, such a UV-induced melanoma or tobacco-induced lung cancer, are driven by a multitude of competing molecular pathways and, as such, are not as successfully managed by a similar approach. Luckily, in the past years, the field of cancer immunotherapy has become more fully developed with the emergence of checkpoint blockade inhibitor therapy. These promising new agents are particularly well suited for tumors with a high mutational burden due to underlying genomic disarray. While still in its infancy, we predict that cancer immunotherapy will offer a better alternative to our current targeted approach and eagerly await the results of several ongoing clinical trials that will elucidate this new direction in cancer therapy.